Call the two numbers "[tex]a[/tex]" and "[tex]b[/tex]". From the problem statement we know that "the sum of the two numbers is 49". So let's write that:
[tex] a + b =49 [/tex]
We also know that "the smaller number is 19 less that the larger number". Let's say that "[tex]a[/tex]" is the larger number. We can then write:
[tex] b = a -19 [/tex]
We now have, 2 equations and 2 unknown numbers. We can solve by substitution.
We already have a substitution for "[tex]b[/tex]" from our second equation, so let's drop that into the other one like so:
[tex] a + b = 49 [/tex]
[tex] a + (a-19)=49[/tex]
[tex]2a-19=49[/tex]
[tex]2a=68[/tex]
[tex]a=34[/tex]
There's our first answer. [tex]a=34[/tex]
We can then use our equation for "[tex]b[/tex]":
[tex]b = a - 19[/tex]
[tex]b = 34 - 19[/tex]
[tex]b = 15[/tex]
There's our second answer. [tex]b=15[/tex]
So:
There's our answer. [tex]a=34 ; b=15[/tex]
Wwe can use our first equation to check our work:
[tex]a+b=49[/tex]
[tex]34+15=49[/tex]
[tex]49=49[/tex] CHECKS